RETHINKING DAWAH MODEL IN THE FOURTH INDUSTRIAL REVOLUTION FOR DIGITAL NATIVE GENERATION - Arifin, Ferdi (Jurnal Dakwah, 2019)
The fourth industrial revolution provides advanced information and technology which leads people to digital culture. Shifting culture phenomena for digitalization happen in many aspects, and one of them is dawah model. Many religious messengers use social media, which is a part of new media product of advanced information and technology, for delivering Islamic values in a larger scale. Yet, most of them cannot understand the basic information of function and features of social media platforms. Meanwhile, digital natives have been confused by some religious messengers for perspective differences in social media. So, this research examines dawah model in the fourth industrial revolution as a way to find out the precisely medium for conveying Islamic values. The research employs qualitative method to examine the phenomena. The result shows that many religious messengers have been used social media platform but some of them use it inappropriately because of misunderstanding about social media function and features. It also finds that digital native generation needs to be elaborated more clearly about religion by using precisely social media platforms.